NOMA-based retrodirective frequency diverse array for multi-user communication - Bello, Hilal; Rosdiadee, Nordin *; Ahmed, Haroon; Chen, Yumin (Elsevier, 2024)
Frequency Diverse Array (FDA) and retrodirective array have found applications in wireless communication networks, offering cost-effective and efficient beamforming capabilities. In this paper, a novel concept of the retrodirective frequency diverse array (RFDA) is introduced, which empowers each array element to handle multiple communication channels, thereby enabling support for multiple users. This is made possible by utilizing the non-orthogonal multiple access (NOMA) scheme. The antenna elements are organized in a uniform circular array configuration. The system supports the multitude of users by assigning them into distinct clusters based on the serving antenna and then allocating transmit power to each user based on their respective channel conditions and distances from the base station. Consequently, efficient schemes for user clustering and power allocation tailored to the NOMA-RFDA system are developed. As a result, multi-user connectivity is achieved while maintaining low design costs. The simulation outcomes affirm that the proposed system attains superior performance in terms of both data rate and energy efficiency when compared to similar reference schemes.